Psychological Shift in Partners of People with Multiple Sclerosis Who Undertake Lifestyle Modification: An Interpretive Phenomenological Study - Neate, Sandra L.; Taylor, Keryn L.; Jelinek, George A.; De Livera, Alysha M.; Brown, Chelsea R.; Weiland, Tracey J. (Frontiers in Psychology, 2018)
Introduction Being in an intimate relationship with a person with multiple sclerosis (MS) may have a substantial impact on the partner’s quality of life. Existing research has largely focused on negative impacts of MS for both people with MS (PwMS) and their partners and has sampled the population of partners of PwMS who have primarily adopted standard medical management only. Modifiable lifestyle factors have become increasingly recognised in the management of MS symptoms and disease progression. For partners of PwMS who have undertaken lifestyle modification as an additional strategy to minimise disease progression, the impacts, both positive and negative remain unexplored. This research is unique as it focuses on partners of PwMS who have attempted to adopt major lifestyle interventions outside of the prevailing paradigm of MS management. Aim To explore and interpret the lived experiences of partners of PwMS who have adopted lifestyle modification, to understand partners’ attitudes to and experiences of the effect of MS and lifestyle modification on their life, relationship and view of the future. Method Design: a qualitative, interpretive, phenomenological study using semi-structured interviews. Participants: English-speaking; aged 18 years or more; in a spousal relationship for 12 months or more with a person with MS who had attended a residential lifestyle educational intervention and undertaken lifestyle modification. Analysis: Interviews were recorded, transcribed verbatim and thematically analysed using Nvivo software. Results Twenty-one partners were interviewed. This paper reports one of the study’s themes, the psychological shift experienced by partners of PwMS. Sub-themes included adaptation; loss and grief; difficult emotions; reframing, re-evaluating and re-prioritising; hope and optimism; empowerment and taking control; and self-awareness, greater understanding and personal growth. Conclusion Partners of PwMS who have undertaken lifestyle modification experienced a broad range of psychological adjustments. Whilst reflecting the potential difficulties that partners of PwMS may experience, this group experienced a range of positive psychological changes that add to the literature regarding partners’ potential experiences and may provide hope for those in partnerships with people with MS. This study provides themes to potentially inform a quantitative study of a larger population of partners of PwMS.